2020
DOI: 10.1140/epjqt/s40507-020-00086-4
|View full text |Cite
|
Sign up to set email alerts
|

A conformal array of microfabricated optically-pumped first-order gradiometers for magnetoencephalography

Abstract: An array of 21 first-order gradiometers based on zero-field optically-pumped magnetometers is demonstrated for use in magnetoencephalography. Sensors are oriented radially with respect to the head and housed in a helmet with moveable holders which conform to the shape of a scalp. Our axial gradiometers have a baseline of 2 cm and reject laser and vibrational noise as well as common-mode environmental magnetic noise. The median sensitivity of the array is 15.4 fT/Hz1/2, measured in a human-sized magnetic shield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 24 publications
(31 reference statements)
1
53
0
2
Order By: Relevance
“…Recent work has shown that inherent OPM-gradiometers (i.e. OPMs where the same light is passed through two separate vapour cells, eliminating the need for digital subtraction and consequently the noise increase) are possible to construct ( Nardelli et al, 2020 ). However, axial gradiometers would require cells to be stacked on top of one another (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that inherent OPM-gradiometers (i.e. OPMs where the same light is passed through two separate vapour cells, eliminating the need for digital subtraction and consequently the noise increase) are possible to construct ( Nardelli et al, 2020 ). However, axial gradiometers would require cells to be stacked on top of one another (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This is arguably more of a problem for OP-MEG than for SQUID-MEG since SQUID-MEG typically uses gradiometers which provide inherent noise reduction (Hämäläinen et al ., 1993). While there are gradiometer OP-MEG designs (Nardelli et al ., 2020; Zhang et al ., 2020), our array was based on magnetometers. It has been shown that high SNR OP-MEG data can be achieved even when there is large participant movement (Boto et al ., 2018; Seymour et al ., 2021), but in these scenarios, the timing of the trials is set by an external stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…when someone rotates their head the magnetic field designed to keep zero field in one orientation will be incorrectly applied to a different orientation). We do not investigate this effect here but note that it could be mitigated by operating sensors in a closed loop mode (Nardelli et al, 2020), learning this field profile directly from the data itself or by utilizing active shielding so as to keep these values to a minimum (Holmes et al, 2018(Holmes et al, , 2019Iivanainen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We note that when a participant moves, one could incorporate linear gradient terms. These would be quite beneficial for very low frequency studies (<3Hz), designing a model informed closed loop OPM systems (Nardelli et al, 2020) or for informing coil currents in active shielding systems (Holmes et al, 2019). However, for simplicity we will ignore these higher order terms here and just focus on the benefits of using a very simple mean field approximation.…”
Section: Magnetic Interference Is Approximately Spatially Constantmentioning
confidence: 99%
See 1 more Smart Citation